Dyeing of Jute Fabric by Eucalyptus Bark Extract - Dibyendu Bikash Datta; Anindya Majumdar; Debasish Das (Journal of Natural Fibers, 2022)
Traditional dyeing procedures were used to color jute fabrics using a natural dye extracted from eucalyptus bark. A pre-mordanting method was followed to dye the jute fabric in the absence and presence of mordant. Alum, vinegar, copper sulfate (CuSO4), alum+CuSO4, vinegar+CuSO4, were used as mordants. Each of the dyed materials was examined in terms of color strength (K/S) and CIELab values. Dyed fabrics were tested for wash, rubbing (dry and wet), and light fastness values. Jute-dyed fabrics without mordants revealed a reddish-brown shade, whereas fabrics dyed with other mordants showed light brown to dark brown shades. Except for unmordanted fabrics that showed moderate to good wash fastness, all fabrics showed good colorfastness to washing. All fabrics showed excellent colorfastness under light and dry rubbing. Apart from the unmordanted fabrics, which had moderate to good wet rubbing fastness, the fabrics had good wet rubbing fastness.